Participation in structured programming may prevent unhealthy weight gain during the summer in school-aged children from low-income neighbourhoods: feasibility, fidelity and preliminary efficacy findings from the Camp NERF study. - Hopkins, Laura C; Holloman, Christopher; Melnyk, Bernadette; Fristad, Mary; Goodway, Jacqueline D; Kennel, Julie A; Eneli, Ihuoma; Gunther, Carolyn (Public Health Nutrition, 2019)
Objective: Evaluate the feasibility, fidelity and preliminary efficacy of Camp NERF to prevent unhealthy weight gain and promote healthy behaviours in children during the summer.Design: Camp NERF was an 8-week, multicomponent, theory-based programme coupled with the US Department of Agriculture's Summer Food Service Program. Twelve eligible elementary-school sites were randomized to one of three treatment groups: (i) Active Control (non-nutrition, -physical activity (PA), -mental health); (ii) Standard Care (nutrition and PA); or (iii) Enhanced Care (nutrition and PA, plus cognitive behavioural techniques) programming. Efficacy was determined by assessing mean change by group in child outcomes using hierarchical linear regression models.Setting: Low-income, urban neighbourhoods in Columbus, OH, USA.ParticipantsEconomically disadvantaged, racial minority children of elementary school age (kindergarten-5th grade).Results: Eighty-seven child-caregiver dyads consented; eighty-one completed pre- and post-intervention assessments resulting in a 93·10 % retention rate. Delivery of the intended lesson occurred 79-90 % of the time. Of the children, 56·98 % (n 49) were female; 89·53 % (n 77) were Black. Overall mean change in BMI Z-score from baseline to post-intervention was -0·03 (se 0·05); change in BMI Z-score did not differ significantly between treatment group. Change in nutrition, PA, mental health or psychosocial outcomes did not differ between groups.Conclusions: Results from the current study demonstrate feasibility and fidelity, yet no intervention effect of Camp NERF. Instead, findings suggest that participation in structured programming of any type (health behaviour-related or not) may prevent unhealthy summer weight gain. Additional studies are needed to confirm findings. Results have implications for child nutrition policy addressing the issue of summer health.